Development and Validation of Simple LC–MS-MS Assay for the Quantitative Determination of Ticagrelor in Human Plasma: its Application to a Bioequivalence Study. (31st January 2019) - Chae, Soo-In; Yoo, Hee Jo; Lee, Su-Yeon; Chung, Eun Kyoung; Shim, Wang-Seob; Lee, Kyung-Tae
Abstract: A sensitive, rapid, reproducible and reliable high-performance liquid chromatography-electrospray ionization tandem mass spectrometric method has been developed and fully validated for the determination of ticagrelor in human plasma using ticagrelor-d7 as an internal standard (IS) after one-step liquid–liquid extraction with ethyl acetate. Ticagrelor and IS were detected in the multiple reaction monitoring mode at m/z transition 523.4 > 127.0 and 530.4 > 127.0, respectively. Chromatographic separation was performed on a Phenomenex Luna® C18 column using a mobile phase consisting of 0.1% formic acid in water–acetonitrile (20:80, v/v) at a flow rate of 0.2 mL/min. The retention times of ticagrelor and IS were 1.03 min and 1.02 min, respectively. The calibration curve was linear [correlation coefficient ( r ) ≥ 0.9991] over the concentration range of 2–1, 500 ng/mL. Intra- and inter-day precisions ranged from 1.0% to 4.9% and from 1.8% to 8.7%, and the accuracy ranged from 97.0% to 105.9% and from 97.5% to 102.9%, respectively. The developed method was fully validated with respect to selectivity, linearity, lower limit of quantitation, recovery, matrix effect and stability. This validated method was successfully applied to the bioequivalence study of ticagrelor in 44 healthy Korean male volunteers.